2003
DOI: 10.1074/jbc.m207903200
|View full text |Cite
|
Sign up to set email alerts
|

Liver Receptor Homologue-1 Mediates Species- and Cell Line-specific Bile Acid-dependent Negative Feedback Regulation of the Apical Sodium-dependent Bile Acid Transporter

Abstract: Intestinal reclamation of bile salts is mediated in large part by the apical sodium-dependent bile acid transporter (ASBT). The bile acid responsiveness of ASBT is controversial. Bile acid feeding in mice results in decreased expression of ASBT protein and mRNA. Mouse but not rat ASBT promoter activity was repressed in Caco-2, but not IEC-6, cells by chenodeoxycholic acid. A potential liver receptor homologue-1 (LRH-1) cis-acting element was identified in the bile acid-responsive region of the mouse but not ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
185
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(196 citation statements)
references
References 40 publications
11
185
0
Order By: Relevance
“…Previous research has shown that unlike rabbits, mice, and human beings, the rat ASBT gene is not regulated via a negative feedback mechanism by BAs.49 -53 BA responsiveness of ASBT is mediated by FXR-dependent activation of small heterodimer partner and subsequent inhibition of liver receptor homologue-1.52 , 53 The rat ASBT promoter lacks a functional liver receptor homologue-1 cis-acting element, and rat ileum does not express the liver receptor homologue-1 protein. 54 Our finding that ASBT protein levels are not increased in neonatal rats gavaged with BAs is consistent with these previous studies. It is compelling, therefore, that in our studies neonatal rats with NEC have statistically significantly increased ileal ASBT in conjunction with increased levels of ileal BA.…”
Section: Discussionsupporting
confidence: 93%
“…Previous research has shown that unlike rabbits, mice, and human beings, the rat ASBT gene is not regulated via a negative feedback mechanism by BAs.49 -53 BA responsiveness of ASBT is mediated by FXR-dependent activation of small heterodimer partner and subsequent inhibition of liver receptor homologue-1.52 , 53 The rat ASBT promoter lacks a functional liver receptor homologue-1 cis-acting element, and rat ileum does not express the liver receptor homologue-1 protein. 54 Our finding that ASBT protein levels are not increased in neonatal rats gavaged with BAs is consistent with these previous studies. It is compelling, therefore, that in our studies neonatal rats with NEC have statistically significantly increased ileal ASBT in conjunction with increased levels of ileal BA.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, Asbt expression is regulated by bile acids through an activation of the nuclear farnesoid X receptor FXR. However, whereas in rabbits, mice and humans Asbt expression is under negative-feedback control by bile acids (Chen et al 2003;Neimark et al 2004;Li et al 2005), in rats Asbt expression was not regulated by alterations of ileal bile acid concentration (Arrese et al 1998). This could be explained by the absence of the liver receptor homologue-1 (LRH-1) transcription binding site in the rat Asbt promoter, by which FXR regulates Asbt expression in rabbits and mice (Chen et al 2003;Li et al 2004).…”
Section: Functional Properties and Expression Patterns Of The Individmentioning
confidence: 97%
“…FTF in the Adult-Converging evidence suggests that FTF basically operates the enterohepatic cholesterol/BA cycle by activating liver BA production and export via CYP7A1 and mrp3 (14 -17,34), intestinal BA absorption via ASBT (21), and BA reentry from intestinal cells into portal blood via mrp3 (20). Short term overexpression of hepatic FTF in transgenic TgF35 mice provides compelling in vivo support for the activating effect of FTF on CYP7A1 and SHP.…”
Section: Discussionmentioning
confidence: 99%
“…A model emerged whereby FTF would act as a "competence" factor driving the BA pathway, subject to negative feedback regulation by interaction of FTF with orphan receptor SHP, activated by the BA receptor FXR and by FTF itself (15,16,18,19). Additional reports associated further FTF action with membrane transporters of the enterohepatic BA recycling system (20,21) and with pancreatic cholesterol esterase (22), all of which pointing to an important systemic role for FTF in adult cholesterol/BA homeostasis.…”
mentioning
confidence: 99%